Some New Explicit Values of Quotients of Ramanujan’s Theta Functions and Continued Fractions - Nipen Saikia (International Journal of Mathematics and Mathematical Sciences)
We evaluate some new explicit values of quotients of Ramanujan’s theta functions and use them to find explicit values of Ramanujan’s continued fractions.